The Lower Motor Neuron Impairment in the Central Nervous Lesion - HARA, Yukihiro (Rihabiritēshon igaku, 2000)
Several authors have reported that disuse might not be a major factor of muscle wasting in hemiplegic patients with stroke. A number of published investigations have shown that pathological spontaneous activity can occur in electromyographic studies in upper motor neuron lesions. There have been some reports that the decrease of hemiplegic side M-potential reflects the drop of motor unit numbers. Most of them have estimated that pathological spontaneous activity in hemiplegic muscles might due to transsynaptic degeneration. The submaximal stimuli can evoke a sample of motor unit action potentials of S-MUAPs in the F-response entirely representative of the relative numbers of surface detected S-MUAPs of different sizes. The motor unit number estimation (MUNE) was investigated among the bilateral abductor pollicis brevis (APB) muscles in seven healthy normal controls and fifteen stroke patients with moderate-to-severe hemiplegia. The needle EMG was examined in hemiplegic side APB. The average S-MUAP on each APB muscle was calculated from a selected population of F-wave responses. The MUNE was calculated by dividing the negative peak amplitude measured from the average S-MUAP waveform into corresponding values measured from a maximum M-potential. There was no statistically difference between the both sides motor units number among normal subjects and this MUNE method also revealed the good reproducibility in them. The needle EMG revealed the spontaneous activity in hemiplegic APB muscles at 3-4 months after the onset. The motor unit number on the hemiplegic side was significantly lower than on the unaffected side (p<0.05, Mann-Whitney test) among stroke patients. About one year later, most stroke patients revealed no spontaneous activity by needle EMG but the motor unit decrement in hemiplegic side was also recognized by the MUNE method among them. The motor unit could decrease in the moderate-to-severe hemiplegic muscle due to the trans-synaptic degeneration secondary to the upper motor neuron lesion. Some investigations, however, reported that there was no significant difference in morphometrical anterior horn cell number between the affected and unaffected sides in strokes. The transsectional areas of anterior horn cells associated with the hemispheric lesional side were reported to be significantly decreased compared with those of the unaffected sides in patients and normal subjects. The motor units may remain morphometrically unchanged in their number but the functional motor units number in the hemiplegic side might decrease because the loss of trophic effect from the upper motor neurons could alter the functional state of anterior horn cell in the affected side. The investigation and therapy for the muscle wasting should be proceeded more for the rehabilitation in upper motor neuron lesions.